Pelatihan Khusus Ibu Rumah Tangga untuk Bayi dan Anak yang Sakit atau Tersedak: Training for Housewives for Sick or Choking Infants and Children - Nova Maryani; Gina Puspita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Choking is one of the most common emergencies experienced by babies and children that must handled quickly. Handling of choking needs attention to prevent complications that can lead to death. The need for proper handling in cases of choking required to be given to the community, including housewives in Pakualaman. This training activity aims to increase public skill, especially among housewives, in recognizing sick or choking babies and children; besides that, they are also expected to provide appropriate treatment if they find cases of sick or choking babies and children. Training activities are implemented through counseling and direct practice, while evaluation is obtained by distributing questionnaires before and after training activities. The evaluation results indicated an increase in the trainees' knowledge in recognizing sick or choking infants and children and managing them at home.